GENESIS OF NOTARIAL SYSTEM. AUSTRIAN PERIOD IN BUKOVYNA - Kovbas, Igor; Krainii, Pavlo (Scientific works of Kyiv Aviation Institute. Series Law Journal "Air and Space Law", 2022)
Purpose: the research on the genesis of the institute of notary in Northern Bukovyna as a part of the Austro-Hungarian Empire in the second half of the XIX century - the first half of the XX century. Methods of research: the use of the historical method in combination with other general and special scientific research methods such as the system method, analysis and synthesis. Applying such methods allowed us to define the political, social and cultural prerequisites for the establishment of a notary institute in Bukovyna in the specified period and to analyse the legislation governing the legal regulation of the notary. Results: the development of the notary was conditioned by specific transformations in the state system, which was constantly under the influence of the state and caused qualitative changes, which were expressed in the creation of new state institutions, including notaries. The legal nature of the notary that was established in Bukovyna allows us to speak of it as an institution of preliminary proceedings, the legal basis for which was the publication of the appropriate document - a patent. Its establishment was conditioned by the citizens’ growing level of culture and education resulting from the undeniable influence of the metropolis. Such a phenomenon led to particular qualitative changes in the provision of both private and public services. Eventually, systematic implementation of the European legal tradition of the state bodies functioning that provide a high level of legal development of society occurred. The valid notarial procedure on the territory of Bukovyna served as the main normative document that regulated the notary's activities and determined its further formation. Discussion: the study of the institute of notaries in Bukovyna in the Austrian period is crucial for understanding its origins and influence on public life in the region. Due to its establishment, the legal status of notaries was detailed, a separate mechanism for selection for such positions was determined, and this institution's appropriate organisational and legal structure was introduced. Legal forms of notaries' activity and their interaction with the local population were established, which directly influenced the region's culture and legal literacy.